Requirement of an early activation of BDNF/c-fos cascade in the retrosplenial cortex for the persistence of a long-lasting aversive memory - Katche, Cynthia Lorena (2015)
During the past few years, there has been growing interest in the role of the retrosplenial cortex (RSC) in memory processing. However, little is known about the molecular changes that take place in this brain region during memory formation. In the present work, we studied the early post-training participation of RSC in the formation of a long-lasting memory in rats. We found an increase in c-Fos levels in the anterior part of the RSC (aRSC) after inhibitory avoidance (IA) training. Interestingly, this increase was associated with memory durability, since blocking c-Fos expression using specific antisense oligonucleotides (ASO) impaired long-lasting retention 7 days after training without affecting memory expression 2 days after training. In addition, we showed that BDNF is one of the upstream signals for c-Fos expression required for memory persistence, since blocking BDNF synthesis prevents IA training-induced increase in c-Fos levels in aRSC and affects memory persistence. In addition, we found that injection of BDNF into aRSC around training was sufficient to establish a persistent memory and that this effect was prevented by c-fos ASO infusion into the same structure. These findings reveal an early post-training involvement of aRSC in the processing of a long-lasting aversive memory.